An Investigation of the Altman Z-Score Measure and the Return on Equity (ROE) of Firms in the Entergy Industry - Willey, Thomas; Bhagwat, Yatin; DeBruine, Marinus (Archives of Business Research, 2023)
This research measures the relationship between the Altman Z-Score, a measure of a firm’s financial health, and the Return on Equity (ROE), a measure of a firm’s profitability for a sample of companies in the Energy industry. The period of the study covers 2014 to 2020 and uses linear regression to examine the relationship between ROE (dependent variable) and the Z-Score (independent variable). Our initial data set contains three hundred and twenty-nine (329) energy-related firms traded on fifty-one (51) world markets. Our initial hypothesis is that a positive and statistically significant relationship exists between the two variables over the examined period. Further research will look at the relationship in other sectors of the markets.